Analýza chromosomu W u skvrnopásníka lískového, Lomaspilis marginata - Demková, Miriam (Jihočeská univerzita, 2022)
The aim of this master thesis was to analyse variability of sex chromosomes in Lomaspilis marginata (Geometridae). Several families of this species were tested for the presence of sex chromatin and also for their variability in the W chromosome composition using comparative genomic hybridization. My results of this study indicated existence of at least three different types of the W chromosome in the investigated species.
Analysis of the W chromosome in the clouded border (Lomaspilis marginata)
Keywords: lepidoptera; lomaspilis; chromosomes; CGH; barcoding